Assessment of critical rainfall scenarios for slope stability analyses based on historical rainfall records in Singapore - Kim, Yongmin (2022)
Rainfall-induced slope failure occurs in many countries including Singapore where slopes are mostly covered with residual soils. Although the significance and impact of rainfall infiltration in inducing slope failures are widely investigated, there have been diverse conclusions regarding the relative roles between soil and rainfall to slope failures under various environmental conditions. In this study, parametric studies were carried out for seven rainfall scenarios and two soils to explore the critical rainfall scenarios affecting the slope stability in Singapore. Special attention was given to the analyses of intensity and duration of the rainfall based on historical rainfall data during the period of 1982–2017 in Singapore. A transient seepage analysis was conducted, and the computed pore-water pressures were used in stability analyses to calculate the variation of factor of safety of the slope during rainfall. The results indicated that the slope with low permeability soil is mainly affected by the 5-day rainfall scenario, while the slope with high permeability soil is mainly affected by the maximum daily rainfall scenario in Singapore. Three case studies clearly validated the findings of this study.